2008
DOI: 10.1086/592764
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Depletion of Nearby Young Stellar Associations

Abstract: We estimate cluster ages from lithium depletion in five pre-main-sequence groups found within 100 pc of the Sun: the TW Hydrae association, Chamaeleontis cluster, Pictoris moving group, Tucanae-Horologium association, and AB Doradus moving group. We determine surface gravities, effective temperatures, and lithium abundances for over 900 spectra through least-squares fitting to model-atmosphere spectra. For each group, we compare the dependence of lithium abundance on temperature with isochrones from pre-main-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
177
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(207 citation statements)
references
References 38 publications
28
177
2
Order By: Relevance
“…However, statistically speaking, Li abundances derived in a homogeneous way as done in this paper can be used to determine relative ages of the young associations provided that the associations possess enough members cooler than 5000−4500 K. Our conclusions are similar to those of Mentuch et al (2008), who also found qualitatively good agreement between the Li abundances and the isochronal ages of a small number of stars belonging to the five associations studied here.…”
Section: Lithium Depletion Pattern and The Relative Agessupporting
confidence: 82%
“…However, statistically speaking, Li abundances derived in a homogeneous way as done in this paper can be used to determine relative ages of the young associations provided that the associations possess enough members cooler than 5000−4500 K. Our conclusions are similar to those of Mentuch et al (2008), who also found qualitatively good agreement between the Li abundances and the isochronal ages of a small number of stars belonging to the five associations studied here.…”
Section: Lithium Depletion Pattern and The Relative Agessupporting
confidence: 82%
“…The EW of Li in J024902 A is weaker than in M1−M2 type members of the ≈ 10 Myr TW Hydrae association, but stronger than members of the ≈ 40 Myr old Tucana-Horologium association (Kraus et al 2014). The Li strength is consistent with that of early-M stars in the β Pic MG, suggesting a similar age of ≈ 20 Myr (Mentuch et al 2008;Mamajek & Bell 2014).…”
Section: Feros Observations Of the J024902 Systemsupporting
confidence: 54%
“…This indicates that both stars are young and have an age younger than that of the Pleiades. According to Mentuch et al (2008) early G-type stars in the β Pic moving group and in the Tucanae-Horologium association have similar Li EW to that of TYC 2627-638-1A and TYC 2627-638-1B, and from this we may estimate an age of about 25 Myr with an uncertainty of at least 10 Myr for our objects.…”
Section: Age Estimates Of the Systemsupporting
confidence: 52%